2001
DOI: 10.1083/jcb.200106023
|View full text |Cite
|
Sign up to set email alerts
|

The N domain of Smad7 is essential for specific inhibition of transforming growth factor-β signaling

Abstract: Inhibitory Smads (I-Smads) repress signaling by cytokines of the transforming growth factor-β (TGF-β) superfamily. I-Smads have conserved carboxy-terminal Mad homology 2 (MH2) domains, whereas the amino acid sequences of their amino-terminal regions (N domains) are highly divergent from those of other Smads. Of the two different I-Smads in mammals, Smad7 inhibited signaling by both TGF-β and bone morphogenetic proteins (BMPs), whereas Smad6 was less effective in inhibiting TGF-β signaling. Analyses using delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
185
1
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(196 citation statements)
references
References 37 publications
6
185
1
4
Order By: Relevance
“…These results also indicate that the de novo induction of Smad7 is not a mechanism involved in the inhibitory action of Ac-SDKP. Previous reports indicate that Smad7 is localized in the nucleus and that TGF-␤-mediated nuclear export of Smad7 is associated with its inhibitory effects (38,45); we therefore clarified the influence of Ac-SDKP on Smad7 localization. Although we could not clearly detect endogenous Smad7 in human mesangial cells by the antibody we used (data not shown), we confirmed the localization of Smad7 by the transfection study.…”
Section: Discussionmentioning
confidence: 84%
“…These results also indicate that the de novo induction of Smad7 is not a mechanism involved in the inhibitory action of Ac-SDKP. Previous reports indicate that Smad7 is localized in the nucleus and that TGF-␤-mediated nuclear export of Smad7 is associated with its inhibitory effects (38,45); we therefore clarified the influence of Ac-SDKP on Smad7 localization. Although we could not clearly detect endogenous Smad7 in human mesangial cells by the antibody we used (data not shown), we confirmed the localization of Smad7 by the transfection study.…”
Section: Discussionmentioning
confidence: 84%
“…At 24 h after transfection, cell lysates were prepared, and luciferase activity was measured by the Dual-Luciferase Reporter System (Promega) as described previously [7]. Values were normalized to Renilla luciferase activity.…”
Section: Luciferase Assaymentioning
confidence: 99%
“…Among the R-Smads, Smad2 and Smad3 act in TGF-β, activin and nodal pathways, whereas Smad1, Smad5 and Smad8 act in BMP and anti-Müllerian hormone pathways. I-Smads (inhibitory Smads), including Smad6 and Smad7, bind to type I receptors and prevent phosphorylation of R-Smads, resulting in the inhibition of TGF-β superfamily signalling [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the identified NLS mediates not only LMB-induced nuclear import of intact Smad4 as well as its isolated MH1 domain, but also the nuclear Since the isolated MH1 domains of R-Smads (such as Smad1 and 3) and I-Smads (such as Smad7) also mostly accumulate inside the nucleus (Xiao et al, 2000a;Hanyu et al, 2001;Kurisaki et al, 2001), we were interested to know whether the Smad4 NLS region is conserved among the R-and I-Smads. We aligned the NLS regions of representative R-Smads (Smad1, 2 and 3), Co-Smads (Smad4) and I-Smads (Smad7) in Figure 8a.…”
Section: Smad4 Nls Resembles An Extended Bipartite Nlsmentioning
confidence: 99%